1990
DOI: 10.1007/bf01977626
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of haemoglobin binding of 4,4′-methylenebis(2-chloroaniline)(MOCA) in rats

Abstract: 4,4'-Methylenebis(2-chloroaniline) (MOCA) is used as a curing agent in the production of polyurethane. MOCA is carcinogenic in experimental animals. Haemoglobin adducts have been proposed as dosimeters of aromatic amines for biological monitoring. A quantitative method to determine the adduct has now been worked out in female Wistar rats dosed per os with 3.82, 14.2 and 16.2 mumol/kg 14C-ring labeled MOCA or 0.25 and 0.50 mmol/kg unlabeled MOCA. MOCA bound in decreasing amounts to DNA, RNA and proteins of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Adducts to albumin and Hb are the most frequently studied protein adduct biomarkers for the risk assessment of various toxins. , The binding preference to these two proteins largely depends on the distinct chemical properties of different reactive metabolites. Generally, the binding tendency to Hb is considered to be higher for most reactive metabolites. This is partly due to the more nucleophilic sites in Hb, including free cysteines and N-terminal amino acids, available for Hb to bind with reactive metabolites compared to albumin. However, reactive metabolites of some toxins, such as aflatoxin B1, naphthalene, and benzidine, have been demonstrated to mainly bind to albumin with relatively lower amounts of Hb adducts formed. ,, The different binding sites and membrane permeability of different reactive metabolites may contribute to the preference of their binding to Hb or albumin. Previously, our group has found that the levels of pyrrole–protein adducts in the Hb fraction were higher than that in the plasma fraction collected from rats treated with different dosages of riddelliine, another toxic PA .…”
Section: Discussionmentioning
confidence: 99%
“…Adducts to albumin and Hb are the most frequently studied protein adduct biomarkers for the risk assessment of various toxins. , The binding preference to these two proteins largely depends on the distinct chemical properties of different reactive metabolites. Generally, the binding tendency to Hb is considered to be higher for most reactive metabolites. This is partly due to the more nucleophilic sites in Hb, including free cysteines and N-terminal amino acids, available for Hb to bind with reactive metabolites compared to albumin. However, reactive metabolites of some toxins, such as aflatoxin B1, naphthalene, and benzidine, have been demonstrated to mainly bind to albumin with relatively lower amounts of Hb adducts formed. ,, The different binding sites and membrane permeability of different reactive metabolites may contribute to the preference of their binding to Hb or albumin. Previously, our group has found that the levels of pyrrole–protein adducts in the Hb fraction were higher than that in the plasma fraction collected from rats treated with different dosages of riddelliine, another toxic PA .…”
Section: Discussionmentioning
confidence: 99%
“…For some compounds such as aflatoxin B1, the carcinogenic metabolites bind preferentially to serum albumin (Sabbioni et al 1987). Sabbioni and Neumann (1990) were unable to hydrolyze 4,4-methylene bis(2-chloroaniline) off of albumin from rats sacrificed 24 h after treatment. However, it is presently unclear the utility of albumin adducts for biomonitoring studies.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of MOCA adducts in rat Hb have been made by radiochemical (12), high-performance liquid chromatography (HPLC) with electrochemical detection (13), gas chromatography-mass spectrometry (GC-MS) (13), and by GC with electron capture detection (8). We report here on an improved GC-MS method, using a stable isotope-labeled internal standard, for the determination of MOCA Hb adducts and report on its application to binding studies in the rat.…”
Section: Introductionmentioning
confidence: 99%